2017
DOI: 10.3847/1538-4357/aa8726
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Photoevaporation of Protoplanetary Disks with Consistent Thermochemistry

Abstract: Photoevaporation is an important dispersal mechanism for protoplanetary disks. We conduct hydrodynamic simulations coupled with ray-tracing radiative transfer and consistent thermochemistry to study photoevaporative winds driven by ultraviolet and X-ray radiation from the host star. Most models have a three-layer structure: a cold midplane, warm intermediate layer, and hot wind, the last having typical speeds ∼ 30 km s −1 and mass-loss rates ∼ 10 −9 M yr −1 when driven primarily by ionizing UV radiation. Obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 55 publications
5
90
3
Order By: Relevance
“…Here we find that the advection timescale is significantly exceeding the timescale for the recombination processes. This result stands in contrast to Wang & Goodman (2017) who found adiabatic cooling to play an important role for the thermal balance of their models. There are however a number of important differences in the model setup and assumptions which may contribute to these discrepancies.…”
Section: Transition Discscontrasting
confidence: 96%
“…Here we find that the advection timescale is significantly exceeding the timescale for the recombination processes. This result stands in contrast to Wang & Goodman (2017) who found adiabatic cooling to play an important role for the thermal balance of their models. There are however a number of important differences in the model setup and assumptions which may contribute to these discrepancies.…”
Section: Transition Discscontrasting
confidence: 96%
“…Moreover, the overall profile of the PEW profile (i.e., decreasing with radius) is not changed (see Fig. 8 of Wang & Goodman 2017, Σ PEW ∝ r −2 ). Therefore we believe that the the evolutionary nature and the conclusion in this article are not affected by the updated PEW model.…”
Section: Photoevaporation Modelsmentioning
confidence: 96%
“…2.4). Recently there has been much progress on the PEW models by Wang & Goodman (2017) and Nakatani et al (2018a,b). They performed radiation hydrodynamic simulations including X-ray and UV radiation.…”
Section: Photoevaporation Modelsmentioning
confidence: 99%
“…Nonetheless, the ability to reproduce the observed line intensities and their approximate profiles is an important requirement for a viable photoevaporation model. One example is the observation of a blue-shift in the [OI] line at 6300Å, which immediately points to a warm quasi-neutral wind, hence ruling out EUV-driven photoevaporation, which produces a fully ionised wind, as in the case of the recent simulations by Wang & Goodman (2017b). In this context, we have calculated here line intensities and line profiles from our new models, via a post-processing of the hydrodynamical grids through the 3D photoionisation and dust radiative transfer code MOCASSIN (Ercolano et al 2003(Ercolano et al , 2005(Ercolano et al , 2008a, and showed that these are in agreement with current observational data.…”
Section: Transition Disc Demographicsmentioning
confidence: 86%